2022
DOI: 10.1155/2022/6722427
|View full text |Cite
|
Sign up to set email alerts
|

Computational Intelligence-Based Model for Exploring Individual Perception on SARS-CoV-2 Vaccine in Saudi Arabia

Abstract: Countries around the world are facing so many challenges to slow down the spread of the current SARS-CoV-2 virus. Vaccination is an effective way to combat this virus and prevent its spreading among individuals. Currently, there are more than 50 SARS-CoV-2 vaccine candidates in trials; only a few of them are already in use. The primary objective of this study is to analyse the public awareness and opinion toward the vaccination process and to develop a model that predicts the awareness and acceptability of SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Machine learning approaches used supervised classification algorithms to extract information regarding sentiment polarity. Classical machine learning models mainly included naïve Bayes, support vector machine, random forest, decision tree, and logistic regression [ 60 , 61 , 67 , 70 , 76 ]. Additional machine learning techniques for polarity classification were Microsoft Azure cognitive services, Amazon Web Services (AWS), and Baidu’s AipNLP [ 59 , 64 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Machine learning approaches used supervised classification algorithms to extract information regarding sentiment polarity. Classical machine learning models mainly included naïve Bayes, support vector machine, random forest, decision tree, and logistic regression [ 60 , 61 , 67 , 70 , 76 ]. Additional machine learning techniques for polarity classification were Microsoft Azure cognitive services, Amazon Web Services (AWS), and Baidu’s AipNLP [ 59 , 64 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…These sentiment analysis studies showed that public sentiments were associated with real-time news, internet information, public health events, the number of COVID-19 cases, vaccine development, the pandemic, and announcements of political leaders or authorities [ 7 , 21 , 27 , 31 , 51 , 52 , 55 , 56 , 58 , 65 ]. Although public sentiments on COVID-19 vaccines varied significantly over time and geography [ 7 , 33 , 39 ], positive sentiments were more prevalent than negative ones regarding COVID-19 vaccines [ 7 , 19 , 20 , 22 , 25 , 29 , 33 , 41 - 44 , 46 , 47 , 51 , 57 , 60 , 62 , 65 , 70 , 72 , 76 , 78 , 84 , 85 ], with trust and anticipation being the predominant emotions [ 20 , 23 , 32 , 37 , 50 , 54 , 58 ]. However, some other studies found that negative sentiments overwhelmed positive ones, with fear being the dominant emotion [ 53 , 59 , 64 , 66 , 71 , 73 , 79 - 82 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations